2012
DOI: 10.1002/pi.4349
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear phase‐separation behavior of poly(methyl methacrylate)/poly(styrene‐co‐maleic anhydride) blends

Abstract: The nonlinear phase‐separation behavior of poly(methyl methacrylate)/poly(styrene‐co‐maleic anhydride) (PMMA/SMA) blends over wide appropriate temperature and heating rate ranges was studied using time‐resolved small‐angle laser light scattering. During the non‐isothermal process, a quantitative logarithm function was established to describe the relationship between cloud point (Tc) and heating rate (k) as given by Tc = Alnk + T0, in which the parameter A, reflecting the heating rate dependence, is much differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…53 The cloud point is just the apparent initial temperature of phase separation during non-isothermal heating process. It is found that the slopes A are very similar for unlled and lled PMMA/ SAN (57/43) systems, indicating that the existence of CRGO has no effect on the sensitivity of the heating rate dependence of cloud point for PMMA/SAN blend with the near-critical composition.…”
Section: Effect Of Crgo On the Non-isothermal Phase Separation Behavimentioning
confidence: 99%
“…53 The cloud point is just the apparent initial temperature of phase separation during non-isothermal heating process. It is found that the slopes A are very similar for unlled and lled PMMA/ SAN (57/43) systems, indicating that the existence of CRGO has no effect on the sensitivity of the heating rate dependence of cloud point for PMMA/SAN blend with the near-critical composition.…”
Section: Effect Of Crgo On the Non-isothermal Phase Separation Behavimentioning
confidence: 99%
“…Our previous work has also proven that the WLF-like equation can perfectly describe the phase-separation behavior of the PMMA/SAN blend investigated by SALLS within the temperature range of T g ~ T g + 100 K [13]. Considering the results above, it should be logical that the DWLF equation can also describe the phase separation behavior of polymer blends at higher temperature above T g + 100 K. Here, the data of the phase separation of the amorphous/amorphous polymer blend (PMMA/SMA) with a lower critical solution temperature (LCST) character, which have been described by the Arrhenius equation in our previous paper [29], were re-examined. The shift factors investigated by SALLS are calculated from:αT=ττs…”
Section: Resultsmentioning
confidence: 99%
“…The critical composition of PMMA/SMA blend is close to 60/40. 46 Hence, the nearcritical composition (60/40) and the off-critical composition (80/20) were selected as our model blend matrix. Furthermore, all the investigated isothermal annealing temperatures were above T g + 100 C. Therefore, the Arrhenius equation should be attempted to describe the phase separation behavior of PMMA/ SMA blends and PMMA/SMA/HSNTs nanocomposites, rather than the WLF equation.…”
Section: Effect Of Hsnts On the Isothermal Phase Separation Behavior mentioning
confidence: 99%
“…When the temperature is above T g + 100 C, the whole chain of polymer can move, and the temperature dependence of relaxation process follows the Arrhenius equation. The temperature dependence of diffusion coefficient, 43 mobility 44 for polymeric materials and phase separation behavior for binary polymer blends, 45,46 the apparent activation energy and the temperature dependence of relaxation time for aqueous polymer solutions 47 can be described by the Arrhenius equation. It is a doubt that whether the incorporation of nanollers may affect the applicability of Arrhenius equation to the phase separation behavior of blend matrix above T g + 100 C.…”
Section: Introductionmentioning
confidence: 99%